Purity and composition of cannabis, heroin and ecstasy samples used in bursa region - Nerkis, Salih; Oruç, H. Hüseyin (Journal of Dependence, 2006)
Objective: The aims of this study were to determine the purity and composition of 21 cannabis, 55 heroin and 65 ecstasy samples seized by law enforcement agencies in Bursa region, and to discuss the probable risks of determined active substance levels and additives for humans using these drugs.Method: The samples were analysed by gas chroma-tography/mass spectrometry (GC/MS) and infrared spectrometry (FTIR).Results: The mean concentrations of tetrahidrocanna-binol (THC) in cannabis, diacetylmorphine in heroin samples and 3,4-methylenedioxymethamphetamine (MDMA) in ecstasy tablets were found to be 2.67 %, 41.51 % and 35.10 %, respectively. Griseofulvin, caffeine, and paracetamol derivates were found in heroin samples, while dexamphetamine, N-formilamphetamine, amphetamine, metamphetamine, caffeine, theophylline, quinine, yohimbine, methaqualone, barbital, phenobarbital, bromazepam, piracetam, cinnarizi-ne, artane, vanillin, lactose, dextrose, sorbitol, sucrose, calcium phosphate, sodium thiosulfate and face powder were found in ecstasy samples.Conclusion: The purity of heroin and ecstasy samples were highly variable. THC levels in cannabis samples were within normal limits. THC amounts in cannabis may be a serious risk for user health only when cannabis is used in high amounts and with alcohol, whereas the active substance levels and some additives in heroin and ecstasy could be a direct serious risk factor for user health.
Keywords: Cannabis; heroin; ecstasy (MDMA); purity; Bursa